PENGARUH KESELAMATAN KESEHATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT COLORPAK INDONESIA TBK - NAPITUPULU, BONAR BJ; Yanuar, Hanif Fadli; cahya kumoro, Dwi Ferdiyatmoko (Jurnal Bisnis Manajemen dan Akuntansi, 2026)
This study aims to understand, analyze, and identify the extent of the "Influence of Occupational Health Safety (K3) and Work Discipline on the Performance of Production Employees at PT Colorpak Indonesia Tbk". Occupational Health Safety (K3) and Work Discipline are two of the various factors that influence Employee Performance. The population in this study was 60 production employees at PT Colorpak Indonesia Tbk. The sample was taken using a non-probability sampling technique with a saturated sampling technique, namely by using the entire population as a sample of 60 people. The collected and processed data will then be tested using descriptive statistical tests, validity tests, reliability tests, classical assumption tests, correlation tests, coefficient of determination tests, regression tests, and hypothesis tests using the SPSS (Statistical Program for Social Science) Ver.27 program. The results of this study indicate that there is a positive and significant influence between occupational health safety (K3) on employee performance, namely t count > t table (13.501 > 2.00172). There is a positive and significant influence between work discipline on employee performance, namely t count > t table (16.368 > 2.00172). There is a positive and significant influence between occupational health and safety (K3) and work discipline together on employee performance, namely F count > F table (155.252 > 3.16). With multiple linear regression equation Y = 2.990 + 0.312X1 + 0.595X2.